2003
DOI: 10.1046/j.1468-1293.2003.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 levels may predict virological response in advanced HIV‐1‐infected patients receiving lopinavir/ritonavir‐based therapy

Abstract: ObjectivesTo examine the relationship between levels of the T-cell regulatory cytokine interleukin-7 (IL-7) and CD4 cell counts during immune reconstitution and to assess its prognostic value in advanced HIV-1-infected patients receiving lopinavir/ritonavir-based therapy. MethodsThirty-six HIV-1-infected adults who completed 48 weeks of follow-up visits were included in this prospective study. Patients having failed two or more antiretroviral therapy regimens were treated with lopinavir/ritonavir-based therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…This suggestion is in line with a recent study showing that HIV-1 TAT protein specifically down-regulates cell surface expression of IL-7Ra on CD8 + T cells in a dose-and time-dependent manner [6]. Our results also confirm and extend findings from previous reports that IL-7 plays an important role in regulating lymphopoiesis [3][4][5]. We found that IL-7 levels were correlated negatively with CD4 + and CD8 + T cell subsets expressing IL-7Ra, and that these associations were stronger with CD4 + memory T cell subsets.…”
Section: Il-7 Levelssupporting
confidence: 93%
See 1 more Smart Citation
“…This suggestion is in line with a recent study showing that HIV-1 TAT protein specifically down-regulates cell surface expression of IL-7Ra on CD8 + T cells in a dose-and time-dependent manner [6]. Our results also confirm and extend findings from previous reports that IL-7 plays an important role in regulating lymphopoiesis [3][4][5]. We found that IL-7 levels were correlated negatively with CD4 + and CD8 + T cell subsets expressing IL-7Ra, and that these associations were stronger with CD4 + memory T cell subsets.…”
Section: Il-7 Levelssupporting
confidence: 93%
“…Other factors that influence disease progression have also been identified. We have reported previously that interleukin (IL)-7, a T cell regulatory cytokine, is a new independent predictor of disease progression and virological response to ART in HIV-1-infected adults [3]. We also reported recently that certain chemokines and growth factors known to be involved in HIV-1 pathogenesis, such as IL-15, regulated upon activation normal T cell expressed and secreted and transforming growth factor-b and that share some biological properties with IL-7, do not influence its predictive value [4].…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine interleukin‐7 (IL‐7) has recently received special consideration because of its pivotal role in CD4 T‐cell homeostasis. We, and others, have reported that patients with low CD4 T‐cell counts show elevated levels of circulating IL‐7 and that these levels are inversely correlated with the number of CD4 T cells [5–7]. Moreover, we have shown that IL‐7 levels represent a new, independent predictor of virological response [5].…”
Section: Introductionmentioning
confidence: 76%
“…Plasma samples were stored at −80°C. Levels of IL‐7, RANTES, SDF‐1 and TGF‐β were measured by quantitative sandwich enzyme‐linked immunosorbent assay (R&D Systems, Minneapolis, MN) as previously reported [5]. All samples were thawed at room temperature, kept on ice and assayed in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…IL-7 increases the survival of T cells in part by increasing the expression of antiapoptotic factor Bcl-2. 23 Interestingly, elevated levels of plasma IL-7 have been found in conditions of T-cell depletion, including after chemotherapy and HIV infection, [24][25][26] and IL-7 levels are inversely correlated with CD4 levels. 24,25 These studies support the notion that increased production of IL-7 may be a homeostatic mechanism for regulating T-cell proliferation and possibly thymic output.…”
Section: Introductionmentioning
confidence: 99%